Research on dynamic behavior of train dynamic model of straddle-type monorail. (November 2020) - Yang, Zhen; Du, Zixue; Xu, Zhouzhou; Zhou, Junchao; Hou, Zhongwei
This article focus on the dynamic behavior of straddle-type monorail composed of multiple vehicles. The four-vehicle dynamic model of straddle-type monorail considering the coupler force is established on the basis of the coupler dynamic model. The correctness of the model is verified by the real experimental vehicle test of Chongqing straddle monorail line 3 from Huixing station to Changfuroad station. The stable wheel overturning coefficient suitable for monorail is proposed which is used to evaluate the anti-overturning performance of straddle monorail. The vibration response, riding comfort, and dynamic curving behavior are analyzed using the dynamic model. The results show that the vibration response of car body accelerations obtained by single-car model is much different from that obtained by train model. The riding comfort of straddle-type calculated by the single-car model would make large mistake, and a multiple train model is needed. The dynamic curving behavior of straddle-type monorail obtained by the single-car model could represent the dynamic curving behavior well.